Impacts of the 2010 Connecticut School Grounds Pesticide Ban a Decade Later: Part 2. Grounds Quality - Sara M. Tomis; Benjamin L. Campbell; Jason J. Henderson; Victoria H. Wallace (HortTechnology)
Ten years after the Connecticut school pesticide ban, the inability to apply Environmental Protection Agency-registered pesticides on school grounds has altered the management of athletic fields and landscapes. This is part two of a three-part series that documents grounds maintenance changes, grounds quality, and potential transitions to synthetic turf 10 years following this ban. To explore the 10-year impact of the 2010 pesticide ban on quality perceptions and management budgets of school grounds properties, a survey was distributed in 2021 to Connecticut school grounds managers. The results indicate that the quality of Connecticut school grounds has declined since the 2010 pesticide ban, even with an increase in operating budgets. Additional guidance and resources for school grounds managers related to optimizing budgets and management practices to enhance the quality of pesticide-free school grounds are needed.